Implications of Tuberculosis Prevention Smart Book in Elementary School Age Children on Parenting Social Support Approach - Indriatie indriatie; Aida Novitasari; Anita Joeliantina (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Tuberculosis (TB) remains a major public health challenge in Indonesia, particularly affecting vulnerable populations such as elementary school-aged children whose immune systems are not fully developed. Despite ongoing national efforts to mitigate the spread of TB, the incidence among children remains notably high, necessitating innovative prevention strategies. This study aims to evaluate the impact of a specifically designed Tuberculosis Prevention Smart Book on enhancing parental social support approaches towards childhood TB prevention. Employing a quantitative quasi-experimental design with a two-group pretest-posttest format, the research sampled 200 parents of children attending elementary schools in Surabaya. Data were collected through structured questionnaires measuring informational, instrumental, emotional, and reward dimensions of social support. Findings indicate a statistically significant improvement in all dimensions of parental support following the intervention, with p-values below 0.05 for informational, instrumental, and emotional support categories. Notably, the use of the Smart Book facilitated heightened parental awareness, increased proactive caregiving behaviors such as early symptom detection and maintaining hygienic environments, and strengthened emotional engagement with children. However, changes in the reward support dimension were not statistically significant. The study concludes that integrating educational Smart Books into health promotion initiatives markedly enhances parental involvement and social support mechanisms critical for childhood TB prevention. This approach offers a promising avenue for community-based TB control programs, emphasizing the pivotal role of parents in safeguarding child health and curbing TB transmission within educational settings